The red plague affair : a Bannon and Clare case - Saintcrow, Lilith (Saintcrow, Lilith. Bannon & Clare, 2013)
Emma Bannon, Sorceress Prime in service to Queen Victrix, has a mission: to find the doctor who has created a powerful new weapon. Her friend, the mentath Archibald Clare, is only too happy to help. Unfortunately, their quarry is a fanatic, and his poisonous discovery is just as dangerous to Britannia as to Her enemies.